Pengaruh Naungan dan Zat Pengatur Tumbuh terhadap Pertumbuhan dan Hasil Tanaman Kentang Kultivar Atlantik di Dataran Medium - Hamdani, Jajang Sauman, Sumadi; Suriadinata, Yayat Rochayat; Martins, Lourenco (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTUse of shade on the cultivation of  potato in medium altitude is expected to reduce both light intensity and temperature, and therefore is more suitable for potatoes to grow in medium altitude. While the use of growth regulators subtances improving the process of assimilate distribution from the leaves to the tuber. Therefore  use of shade followed by plant growth regulators applications are expected to increase of  growth and yield. The objectives of the experiment were to determine growth and yield of  potato cultivar Atlantik grown  at medium  altitude with different types of shading and  plant growth regulators. The experiment was conducted at an experimental station of the Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang, at an altitude 685 m asl. The experiment was arranged in  a split plot design  consisting of two factors and three replications. The main plots were types of shading (without shading, paranet 45%, UV polyethylene, and corn plant) and the sub plots were combination of plant growth regulators (benzylaminopurine + paclobutrazol), (benzylaminopurine +chloro choline chloride), benzylaminopurine, paclobutrazol, chloro choline chloride).  The results showed that the effect of interaction between shading and plant growth regulator on growth and yield of the potato were not significant. Paranet shade and corn plant shade  increased plant height, leaf area index, tuber weight per plant, yield  per hectar and tuber grade A of potato cultivar Atlantik. Corn plant shading gave potato yield 21.6 ton ha-1 with 64% grade A tuber. Paclobutrazol decreased potato plant  height,  but  increased  number  of  tuber per plant and yielded highest tuber weight of 702.1 per plant (23.3 ton ha-1 ), with 70.9% grade A tuber.    Keywords: Benzylaminopurine, microclimate, paclobutrazol, temperature